POLA ASUH DAN DUKUNGAN KELUARGA TERHADAP PROSES PENYEMBUHANANAK PENDERITA AUTIS DI PUSAT LAYANAN AUTIS KOTA SAMARINDA TAHUN 2016 - Godefridus Bali Geroda (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2016)
Autism is a situation where an engrossed in his own world. This situation is usually encountered for the first time in childhood and entering the mind as well as his own fantasy world and will be even worse in the case of heavy-patient retrospective case series will be immersed in his own hallucinations. This study used a qualitative research design with ethnography approach, by using in-depth interviews and direct observation to acquire the knowledge, attitudes, action and family support in the healing process of children with autism. The results showed that knowledge of family to care of children with autism are already well able to explain the definition, symptoms and resources about autism attitudes towards the care of children with autism are relatively good, although a good attitude is not always accompanied by good results. Actions in carrying families parenting children with autism in the healing process has been good with the hope that his son will be cured of autism. Parenting applied is authoritarian parenting and family support is the closest to people with autism who gave a major influence on the recovery efforts of an autistic child. Who always support in any process of therapy in autism service center or at home.